Adaptive nonsingular terminal sliding mode guidance law against maneuvering targets with impact angle constraint. (April 2015) - Wang, Weihong; Xiong, Shaofeng; Liu, Xiaodong; Wang, Sen; Ma, Lujin
Under the existence of the unknown target acceleration, guidance law that guarantees imposing a predetermined impact angle relative to a maneuvering target's flight direction is proposed in this paper. The prespecified impact angle is defined in terms of a time-varying desired line of sight angle for a maneuvering target. Then, the problem of impact angle guidance law design is transformed to a problem of state tracking. To deal with the unknown target acceleration, an extended state observer is utilized to estimate it instead of simply treating it as zero. In order to avoid the singularity in the terminal phase of guidance and eliminates the need of a priori knowledge of the uncertainty upper bound, an adaptive nonsingular terminal sliding mode control scheme is adopted to design the sliding surface. The switching gain is not necessary to be determined in advance but adjusted according to the adaptive rule. Numerical simulations are implemented to demonstrate the effectiveness of the proposed guidance law.